Benefits and development of assistive technologies for Deaf people's communication: A systematic review - Rodríguez-Correa, Paula Andrea; Valencia-Arias, Alejandro; Patiño-Toro, Orfa Nidia; Oblitas Díaz, Yober; Teodori De la Puente, Renata (Frontiers in Education, 2023)
The development of technologies has made digital accessibility relevant to many everyday processes. Multiple resources have been designed to meet the special needs of a wide variety of people, such as Deaf sign language users, who require inclusive technologies to facilitate their communication in work, educational, and social environments. The objective of this study is to identify assistive technologies that favor and improve communication between Deaf and hearing people. To this end, a systematic review was carried out following the PRISMA checklist and using the Scopus, Web of Science, and PubMed databases. A total of 576 records were identified and subjected to inclusion and exclusion criteria, of which 27 were included in the quantitative synthesis. As a result, technologies based on gesture recognition for the translation of sign language into speech and vice versa, technologies for sign language teaching, technologies for automatic caption generation, technologies based on online content, and technologies based on text and illumination networks were found in the studies. The findings suggest that there is a need for further research into the motivations for developing sign language technologies, as a contribution to the inclusion of Deaf communities in society without linguistic impositions.